Technological and Business Fundamentals for Mobile App Development - Salter, Tamie (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is an essential introductory guide to the knowledge required to develop apps. Chapter by chapter it provides the core principles any person must understand in order to develop mobile applications. It outlines the fundamental skills and knowledge that business and computer science students need to either oversee the development of a mobile app or themselves undertake to develop a mobile app. This workbook will give a holistic overview of the initial stages that must be considered when endeavoring to develop a mobile app. This workbook breaks topics down into core, technical and non-technical. Looking at each topic from all three angles, the core knowledge required for UI, UI for the technical person and UI for the non-technical person. The workbook guides the student through the key components or core of mobile app development and shows all students both the technical requirements and the non-technical requirements of each topic. It will allow all students to pick and choose how deep they wish to delve into the different topics.
Dedication -- Overview -- 1 Overview of Steps and Necessary Skills -- 2 Key Ingredients for a Great App -- 3 Concept Design -- 4 Technology & Technical Development -- 5 Trends/Digital Security/Compliance/Getting Accepted -- 6 Monetization -- 7 Budget/Project Management/Research/Marketing -- Capstone Project - An App for POP DRINKS -- Conclusion -- Glossary -- Bibliography.
Keywords: Internet programming; Electronic commerce; Business information services; Application software; Web Development; e-Commerce and e-Business.; IT in Business; Computer and Information Systems Applications